Morphological development of larvae and juveniles of Prochilodus argenteus - Irũ Menezes Guimarães; Vinícius Augusto Dias Filho; Ana Helena Gomes da Silva; Rafael Silva Santos; William Severi (Ciência Rural)
ABSTRACT: Prochilodus argenteus is an endemic fish species from the São Francisco River basin that is of high economic and environmental importance. The present study aimed to contribute with information to the taxonomic identification of larvae and juveniles of this species. Larvae , obtained from induced spawning of wild animals, were reared in ponds. Individuals were collected daily and classified into larval stages or juvenile phase. Morphological descriptions and morphometric measurements were performed, together with a piece wise linear regression analysis of the body proportions throughout the development process. Individuals in the preflexion stage had a standard length (SL) of 4.48 to 6.64mm, long to moderate body (BH/SL), small to moderate head (HL/SL), and a small to moderate eye (ED/HL). In the flexion stage, the SL varied from 6.60 to 11.00mm, long to moderate body, moderate head, and small to moderate eye. Larvae in the postflexion stage presented SL of 10.54-19.93mm, moderate body, moderate to big head and small eye. The juvenile phase included specimens with a SL of 18.27 to 42.21mm which presented a moderate to high body, big head and small to moderate eye. Regression analysis showed significant moments of change in rate of increase of the body proportions, presenting a change in the growth pattern from allometry to isometry during the early development.